Integration of Artificial Intelligence in Academic Research: To What Extent Do Students' Knowledge, Understanding, and Use Depend on Technology? - Tuti Iriani; Nur Azisah; Yusrina Luthfiana; Bimo Nugroho (International Journal of Engineering, Science and Information Technology, 2025)
The development of artificial intelligence (AI) technology has had a significant impact on higher education. This study aims to assess the level of knowledge, understanding, and use of AI among students in the context of final project preparation. This study uses a quantitative descriptive approach to measure three main dimensions—knowledge, understanding, and practical use (application) in the context of academic research. The population in this study consisted of 172 students from the Faculty of Engineering, Universitas Negeri Jakarta, who were conducting academic research. The sampling technique employed was non-probability sampling, utilizing a purposive sampling approach. Data analysis used exploratory factor analysis (EFA). The results showed that students have excellent knowledge of AI. Meanwhile, the understanding of AI shows varying levels, with the majority falling into the sufficient and low categories, indicating a need to improve AI literacy. The use of AI by students is primarily focused on aspects of writing, research, and document creation, with a reasonably consistent usage pattern and an average duration of 1-2 hours per session. These findings confirm that students actively utilize various AI in the academic process, but still require training and supervision to ensure that AI use can be carried out ethically and responsibly. The results of this study are important as a basis for developing institutional policies and ethical regulations related to the integration of AI into academic processes, as well as a reference for designing effective training programs to improve students' competency in optimally utilizing AI technology.